2022
DOI: 10.1088/1755-1315/1041/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Study on the commitment of oil palm companies to achieve sustainable agriculture in Riau Province from the perspective of pesticide use

Abstract: Oil palm has become the main plantation commodity in Riau Province, Indonesia. As the province with the largest oil palm plantation at around 2.7 million hectares, Riau Province has 19% of Indonesia’s total oil palm plantation area. In the midst of environmental issues such as forest fires or using hazardous chemicals, companies or individuals who own oil palm plantations are trying to obtain sustainability certification from the Roundtable of Sustainable Palm Oil (RSPO). However, many companies have not obeye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…dengan penyebaran serangan kumbang tanduk terbesar mencapai angka 2,717 ha di Kabupaten Indragiri Hilir, 340 ha di Siak, 579 ha di Kampar, 459 ha di Kuansing, dan sisanya menyebar di perkebunan kelapa sawit milik rakyat (Candra et al, 2019). Selama ini pengendalian hama pada tanaman kelapa sawit menggunakan pestisida sintetis yang tidak aman bagi lingkungan dan kesehatan masyarakat (Syafrani et al, 2022).…”
Section: Short Communicationunclassified
“…dengan penyebaran serangan kumbang tanduk terbesar mencapai angka 2,717 ha di Kabupaten Indragiri Hilir, 340 ha di Siak, 579 ha di Kampar, 459 ha di Kuansing, dan sisanya menyebar di perkebunan kelapa sawit milik rakyat (Candra et al, 2019). Selama ini pengendalian hama pada tanaman kelapa sawit menggunakan pestisida sintetis yang tidak aman bagi lingkungan dan kesehatan masyarakat (Syafrani et al, 2022).…”
Section: Short Communicationunclassified
“…Moreover, indiscriminate use of pesticides may also disrupt ecological balance and eventually harm non-target organisms, including beneficial insects and soil microorganisms. A recent study revealed widespread use of conventional pesticides, including Roundtable on Sustainable Palm Oil (RSPO)-prohibited paraquat (Figure 1), in Indonesian E. guineensis plantations, which has underscored the persistence of unsustainable practices despite global sustainability initiatives [28].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical fertilizers have a high level of toxicity to the environment and biodiversity. Other studies have shown that 70% of pesticides used in oil palm plantations are harmful to non-target species [3].…”
Section: Introductionmentioning
confidence: 99%